2015
DOI: 10.1155/2015/680104
|View full text |Cite
|
Sign up to set email alerts
|

Does Intensive Glucose Control Prevent Cognitive Decline in Diabetes? A Meta-Analysis

Abstract: Diabetes mellitus is associated with cognitive decline and impaired performance in cognitive function tests among type 1 and type 2 diabetics. Even though the use of tight glucose control has been limited by a reported higher mortality, few reports have assessed the impact of treatment intensity on cognitive function. We conducted a meta-analysis to evaluate if an intensive glucose control in diabetes improves cognitive function, in comparison to standard therapy. We included 7 studies that included type 1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Intensive glycemic control with medications has not been shown to improve cognition and in fact may worsen it. 9 Exercise and a Mediterranean-style diet may improve cognitive function or prevent or at least delay cognitive decline. 10 Computer-based cognitive rehabilitation interventions designed for individuals with other chronic conditions such as multiple sclerosis have been shown to improve performance on neuropsychological tests and improve quality of life in those who have objective evidence of cognitive problems or subjective concerns.…”
mentioning
confidence: 99%
“…Intensive glycemic control with medications has not been shown to improve cognition and in fact may worsen it. 9 Exercise and a Mediterranean-style diet may improve cognitive function or prevent or at least delay cognitive decline. 10 Computer-based cognitive rehabilitation interventions designed for individuals with other chronic conditions such as multiple sclerosis have been shown to improve performance on neuropsychological tests and improve quality of life in those who have objective evidence of cognitive problems or subjective concerns.…”
mentioning
confidence: 99%
“…15 However, a recent meta-analysis found an improvement in executive functioning domains and processing speed in Type 2 diabetes. 7 Second, exercise has been found to improve cognitive function in patients with prediabetes 3 ; however, a long-term intensive lifestyle intervention did not affect the prevalence of cognitive impairment in the elderly. 5 Third, cardiovascular risk factor control, such as blood pressure management in the Hypertension in the Very Elderly Trial suggested a benefit when controlling blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] At the same time, improvement in the control of diabetes decreases the cognitive impact on patients with diabetes. 7 However, most of these data are derived from elderly adults. There is very limited information regarding the onset of cognitive changes and the prevalence of cognitive decline among middle-aged adults with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis that included only three studies on type 2 diabetes compared the difference in the impact of intensive and conventional glucose control on cognitive performance among patients with diabetes [ 14 ]. The pooled analysis of these three studies, including 3200 individuals with type 2 diabetes, showed the benefits of intensive glucose control therapy on information-processing speed and executive functions, but no difference was observed on attention and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have suggested that cognitive functioning in patients with type 2 diabetes might benefit from several months of improved glycemic control [ 12 , 13 ]. A recent meta-analysis indicated that people with type 2 diabetes performed better in processing speed and executive function but more poorly in memory and attention when on intensive glucose control regimes [ 14 ]. However, this analysis assessed the performance of the participants only at the end of the study.…”
Section: Introductionmentioning
confidence: 99%